CD8+ Resident Memory T Cells and Viral Infection - Wu, Xuejie; Wu, Pin; Shen, Yifei; Jiang, Xiaodong; Xu, Feng (Frontiers in Immunology, 2018)
Tissue resident memory T cells (Trm) are a subset of recently identified memory T cells that mainly reside and serve as sentinels in non-lymphoid peripheral tissues. Unlike the well-characterized circulating central memory T (Tcm) cells and effector memory T (Tem) cells, Trm cells persist in the tissues, do not recirculate into blood, and offer immediate protection against pathogens upon reinfection. In this review, we focus on CD8+ Trm cells and briefly introduce their characteristics, development, maintenance and function during viral infection. We also discuss some unresolved problems, such as how CD8+ Trm cells adapt to the local tissue microenvironment, how Trm cells interact with other immune cells during their development and maintenance, and the mechanisms by which CD8+ Trm cells confer immune protection. We believe that a better understanding of these problems is of great clinical and therapeutic value and may contribute to more effective vaccination and treatments against viral infection.